Managing Quality in Architecture : A Handbook for Creators of the Built Environment - Nelson, Charles (Charles E.) (Elsevier, 2006)
Addresses the questions of how best to manage quality in architecture for the mutual benefit of design practices and their clients. Based on research from the last two decades, it explores the general principles, tools and techniques that can be adapted to the unique culture of any design practice to deliver results.